Xema, a foxi-class gene expressed in the gastrula stage Xenopus ectoderm, is required for the suppression of mesendoderm formation - Suri, Crystal (2005)
The molecular basis of vertebrate germ layer formation has been the focus of intense scrutiny for decades, and the inductive interactions underlying this process are well-defined; only recently, however, have studies demonstrated that the regulated inhibition of ectopic germ layer formation is also critical for patterning the early vertebrate embryo. We report here the characterization of Xema (Xenopus Ectodermally-expressed Mesendoderm Antagonist), a novel member of the Foxi-subclass of winged-helix transcription factors that is involved in the suppression of ectopic germ layer formation in the frog, Xenopus laevis. Xema transcripts are restricted to the animal pole ectoderm during early Xenopus development. Ectopic expression of Xema RNA inhibits mesoderm induction, both by growth factors and in the marginal zone, in vivo. Conversely, introduction of antisense morpholino oligos directed against the Xema transcript stimulates the expression of a broad range of mesodermal and endodermal marker genes in the animal pole. Our studies demonstrate that Xema is both necessary and sufficient for the inhibition of ectopic mesendoderm in the cells of the presumptive ectoderm, and support a model in which Fox proteins function in part to restrict inappropriate germ layer development throughout the vertebrate embryo.